1999
DOI: 10.1046/j.1365-2958.1999.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the C‐terminal domain essential for toxic activity of adenylate cyclase toxin

Abstract: SummaryAdenylate cyclase toxin (CyaA) of Bordetella pertussis belongs to the RTX family of toxins. These toxins are characterized by a series of glycine-and aspartaterich nonapeptide repeats located at the C-terminal half of the toxin molecules. For activity, RTX toxins require Ca 2þ , which is bound through the repeat region. Here, we identified a stretch of 15 amino acids (block A) that is located C-terminally to the repeat region and is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 31 publications
5
42
0
Order By: Relevance
“…Like other intrinsically disordered polypeptides it contains a high content of random coils and is highly hydrated (30)(31)(32). Upon binding calcium, the CyaA RD folds into a stable β-roll structure that facilitates interaction with a cell surface receptor and the translocation of an N-terminal adenylate cyclase domain across the plasma membrane (32)(33)(34)(35)(36). We found that the chimeric passenger domain was secreted efficiently even in the absence of calcium and thereby showed that translocation can proceed efficiently without passenger domain folding.…”
Section: Significancementioning
confidence: 80%
“…Like other intrinsically disordered polypeptides it contains a high content of random coils and is highly hydrated (30)(31)(32). Upon binding calcium, the CyaA RD folds into a stable β-roll structure that facilitates interaction with a cell surface receptor and the translocation of an N-terminal adenylate cyclase domain across the plasma membrane (32)(33)(34)(35)(36). We found that the chimeric passenger domain was secreted efficiently even in the absence of calcium and thereby showed that translocation can proceed efficiently without passenger domain folding.…”
Section: Significancementioning
confidence: 80%
“…A number of previous studies suggest that a region between the repeat domain and the C terminus may be involved in binding this specific receptor. For example, Bejerano et al (14) have described two amino acid "blocks," located after the nonapeptide repeats, in the C terminus of the adenylate cyclase toxin (another member of the RTX family). Block A (15 amino acids) is essential for the toxic activity since it is required for the toxin binding and insertion into the membrane.…”
Section: ␣-Hemolysinmentioning
confidence: 99%
“…HlyA possesses homologous A and B blocks ( Fig. 1), and it has been shown (14) that deletion of a region that includes the last two residues of block A, the connection between the blocks, and the first nine amino acids of block B abolishes the hemolytic activity. Previously, Chervaux and Holland (15) had shown that five point mutations in that region (residues 918, 920, 921, 928, and 932) inhibited hemolysis without affecting protein export.…”
Section: ␣-Hemolysinmentioning
confidence: 99%
“…[86] Accordingly, Ca 2þ ions are required for folding and hence, cytotoxicity of the T1SS secreted proteins. [87][88][89][90] Recent studies provide evidence for an intramolecular translocation ratchet powered by folding of the RTX-domain: Within the "channel-tunnel" system of the T1SS that spans the entire cell envelope, the secreted proteins are transported in an unfolded state, as expected from the channel dimensions [91] ( Figure 4B). The unfolded protein is transported in a C to N direction, leading to initial exposure of the C-terminus and thus the first RTX repeat segment.…”
Section: Potentially Length-dependent Intramolecular Translocation Ramentioning
confidence: 93%